2014
DOI: 10.1016/j.jinsphys.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Hunger is the best spice: Effects of starvation in the antennal responses of the blood-sucking bug Rhodnius prolixus

Abstract: Blood-sucking insects strongly rely on olfactory cues to find their vertebrate hosts. As in other insects with different lifestyles, it has been shown that endogenous and exogenous factors modulate olfactory responses. The triatomine bug Rhodnius prolixus is an important vector of Chagas Disease and a classical model for studies of physiology and behavior. In this species, the behavioral response to host-derived odorants is modulated by both the time of the day and the starvation. Here I investigated the perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
(78 reference statements)
0
19
0
1
Order By: Relevance
“…Larval R. prolixus display reduced electrophysiological responses to ammonia after ingesting a blood meal (Reisenman, 2014). Moreover, engorged triatomine larvae are refractory to host odor stimulation for a prolonged time after feeding (Bodin et al, 2009a) and remain hidden in shelters for several days while their molting is completed.…”
Section: Discussionmentioning
confidence: 99%
“…Larval R. prolixus display reduced electrophysiological responses to ammonia after ingesting a blood meal (Reisenman, 2014). Moreover, engorged triatomine larvae are refractory to host odor stimulation for a prolonged time after feeding (Bodin et al, 2009a) and remain hidden in shelters for several days while their molting is completed.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that any odor-based control strategy should consider that different types of natural odor stimuli (including background odors) often interact (e.g., Chaffiol et al, 2012 , 2014 , see also Section Effects of Background Odor). In addition, it should be considered that the physiological state of the insects (e.g., mating, feeding) as well as learning affects their responses to odors (e.g., Barrozo et al, 2010 ; Saveer et al, 2012 ; Reisenman, 2014 ; Matthews et al, 2016 ; Section Plasticity in the Responses to Semiochemicals).…”
Section: Olfactory Attraction For Monitoring and Trappingmentioning
confidence: 99%
“…In both blood-sucking and herbivorous insects the activity of ORCs can be affected by experience (e.g., long-term odor exposure and sensory adaptation to deterrents; see Section Mating Disruption). Experience can also cause downregulation of olfactory responses according to the feeding/mating status, and the time of the day (e.g., Almaas et al, 1991 ; Fox et al, 2001 ; Takken et al, 2001 ; Glendinning et al, 2009 ; Saveer et al, 2012 ; Stanczyk et al, 2013 ; Anderson and Anton, 2014 ; Claudianos et al, 2014 ; Reisenman, 2014 ). In general, associative learning is not usually represented at this level, although recent work in honeybees revealed that olfactory memories downregulate the expression of specific ORs.…”
Section: Plasticity In the Responses To Semiochemicalsmentioning
confidence: 99%
“…Other important factors influencing the strength of odor guided behavior in insects are related to their physiological state (Gadenne et al, 2016 ). Starving individuals, for example, respond more strongly to food-related odors than satiated ones (Edgecomb et al, 1994 ; Reisenman et al, 2013 ; Reisenman, 2014 ) and the response to sex pheromones depends on the age insects reach sexual maturity (Shorey et al, 1968 ; Landolt and Heath, 1988 ). Similar to some mammals (Serguera et al, 2008 ), the mating status of insects is another intrinsic parameter modulating their olfactory response to sex pheromones (Gadenne et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%